Pengaruh Suasana Lingkungan, Keramahan Tuan Rumah, Serta Aksesibilitas Lokasi terhadap Minat Kunjungan Ulang Wisatawan di Homestay Gardu Pandang Selo - Melania Sintia Dewi; Budi Istiyanto (JURNAL MANAJEMEN DAN BISNIS EKONOMI, 2025)
This study aims to empirically analyze the partial and simultaneous influence of environmental atmosphere, host friendliness, and location accessibility on tourists’ revisit intention at Homestay Gardu Pandang Selo, Boyolali Regency. Tourism growth in this area continues to increase, yet the low rate of repeat visits indicates a gap between visitor expectations and the quality of experience offered. Employing a quantitative causal-associative method, data were obtained from 96 respondents who had stayed at least once, using purposive sampling. Data analysis was performed with multiple linear regression using IBM SPSS Statistics 25. Classical assumption tests confirmed that the regression model met the requirements of normality, multicollinearity, and heteroscedasticity. The results revealed that environmental atmosphere and location accessibility had a positive and significant effect on revisit intention, while host friendliness showed an insignificant effect. Accessibility emerged as the most dominant factor influencing revisit intention, indicating that physical access and travel convenience play a central role in shaping tourist loyalty. The findings emphasize the importance of environmental management and infrastructure development as strategic priorities for homestay managers. Although host friendliness did not show a significant impact, maintaining a warm and consistent hospitality standard remains essential to sustain visitor satisfaction. Overall, this study contributes theoretically by reinforcing behavioral intention theory in tourism and practically by offering insights for community-based tourism management to strengthen destination competitiveness through repeat visitation.